Positive cascade effects of forest fragmentation on acorn weevils mediated by seed size enlargement - Bonal, Raul; HERNÁNDEZ, MARISA; ORTEGO, JOAQUÍN; Muñoz, Alberto; ESPELTA, JOSEP M. (Insect Conservation and Diversity, 2012)
Abstract. 1. Today, forest fragmentation is one of the major threats to biodiversity worldwide. In this context, fragmented populations of specialised forest organisms face an increasing risk of extinction because of factors such as local food scarcity. Nonetheless, the role of food availability may differ depending on organism size, which is expected to determine the energy requirements and mobility between fragments. 2. A field study was carried out on Curculio elephas, a forest beetle with low dispersal potential, whose larval development takes place in oak Quercus spp. acorns. 3. For a similar seed crop per tree, acorn size was larger in isolated oaks than in trees located in forest patches. Thus, fragmentation increased local food availability for C. elephas. Larger acorns enabled larval size to increase, a key fitness proxy associated with individual survival, adult size, and potential female fecundity. Indeed, the number of both adults and larvae was higher in isolated trees than in forest patches. 4. In the current scenario of increasing forest fragmentation, the survival likelihood of specialist insects may strongly depend on their ability to adapt to altered environmental conditions. To the best of our knowledge, this is the first study to report on how some forest insects may take advantage of fragmentation-mediated changes to survive in isolated trees. 5. From a conservation perspective, management policies should preserve isolated trees as a source of seeds and fauna for the natural regeneration of forest ecosystems after unproductive farmlands have been abandoned.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: acorn size; Curculio; Forest fragmentation; forest insects; Global change; individual fitness; larval size